Zázraky na mariánských poutních místech - Tereza Kolmačková (Historie - Otázky - Problémy, 2022)
This study deals with miracles at Marian pilgrimage sites. On the basis of printed pilgrimage books from selected sites — Svatá Hora near Příbram, Stará Boleslav, Hájek near Prague and Tuřany — it shows what types of events were described as miraculous and how people talked about them. It also touches on the role of votive offerings and material objects in miraculous stories.